Vloga polkmetij v preobrazbi slovenskih obmestij - Razpotnik Visković, Nika (Georitem, 2013)
This volume ('The role of part-time farms in the transformation of the urban fringe') discusses the role of part-time farms in the economic, environmental and spatial transformation of the urban fringe. On the basis of the sample of Slovene suburban farms, the impact level of the proximity of workplaces on the mobility of the agricultural workforce was determined. It was also determined if socio-economic characteristics of suburban agricultural economies reflect in the characteristics of farm management and in the environment. This consequently stresses the role of part-time farms in the strengthening of multi-layered agriculture.